Future of health diagnostics. Issue 1 (23rd March 2020) - Lim, Chwee Teck
Abstract: A diagnosis is often the first step to take in order to arrive at a decision on how best to treat a patient. With the emergence of new medical technologies such as wearables, big data, and artificial intelligence, the future of health diagnostics will not only be about timely and precise treatment, but also prevention. Abstract : With the emergence of new medical technologies such as wearables, big data, and artificial intelligence, the future of health diagnostics will not only be about timely and precise treatment, but also prevention.